Efficient coupling of lateral force in GaN nanorod piezoelectric nanogenerators by vertically integrated pyramided Si substrate. (July 2017) - Tsai, Shu-Ju; Lin, Chun-Yeh; Wang, Chiang-Lun; Chen, Jhih-Wei; Chen, Chia-Hao; Wu, Chung-Lin
Abstract: Piezoelectric energy harvesting is a promising technique for scavenging ambient mechanical motion for driving compact, low-power, multi-functional electronic devices. To adapt to various ambient surroundings, the geometric configurations and sizes varied in wide ranges with high operational reliabilities and piezoelectric performance have been regarded as a key for piezoelectric harvester design. Herein, by applying a normal force, we report an innovative structure for harvesting electric energy from bending the obliquely aligned GaN piezoelectric nanorods (NRs) that are integrated in the vertically integrated nanogenerator (VING). The single-crystalline GaN NRs used here were successfully synthesized with obliquely alignments on the pyramided Si substrate by plasma-assisted molecular beam epitaxy (PA-MBE). Using conductive atomic force microscope (c-AFM), a remarkable change in the Schottky barrier height (SBH) between the tip and GaN NR is observed upon bending an oblique-aligned GaN NR. This demonstrates that a remarkably enhanced piezoelectric performance of GaN NRs can be achieved by coupling a lateral force. We anticipate that this work will provide an efficient approach for coupling the lateral loading to enhance the electric potential in piezoelectric NRs-embedded VING, and thus open a new path for efficiently generating electric energy. Graphical abstract: The single-crystalline obliquely aligned GaN nanorods (NRs) were grown on textured-Si substrate by plasma-assisted molecular beam epitaxy (PA-MBE). By applying a normal force, enhanced piezoelectric energy was obtained from bending the obliquely aligned GaN piezoelectric NRs integrated in the vertically integrated nanogenerator (VING). Highlights: The obliquely aligned GaN nanorods (NRs) were grown on pyramided Si substrates by PA-MBE. By applying a normal force, enhanced piezoelectric output was obtained from bending the obliquely aligned GaN piezoelectric NRs integrated in the VING. It provides an efficient approach for coupling the lateral loading to enhance the piezoelectric, piezotronic, and piezo-phototronic performance in piezoelectric NRs- based devices.